How Do I Counsel Parents of a Newly Diagnosed Boy with Haemophilia A? - Kurnik, Karin; Bidlingmaier, Christoph; Olivieri, Martin (Hämostaseologie, 2020)
With the recent approval of improved therapeutic options for patients suffering from haemophilia A such as the extended half-life, recombinant factor concentrates, non-factor VIII replacement therapies like Emicizumab and after consideration of the currently running clinical trials investigating even more advanced approaches, counselling of parents of a newly diagnosed boy with haemophilia A has not become less demanding. Parents need to be informed about the pathophysiology, the chronic nature and the potential risks that are commonly associated with this disease and its treatment, depending on disease severity. Above all, the safety and efficacy of the medicinal drug(s) to be used are of utmost importance, given the impact of non-virus-inactivated plasma-derived factor concentrates in the 1980s. As a consequence, the subsequent development and registration of recombinant clotting factors from mammalian, and recently, even human, cell cultures are seen by many as a breakthrough, although, regarding the product-type-dependent development of inhibitors in previously untreated patients, the discussion is still open. Clinical data for the humanised bispecific antibody Emicizumab in paediatric patients below 2 years of age without inhibitors who suffer from severe haemophilia A are currently limited.
Keywords: haemophilia A; parents; counselling